Assessing 40 years of spatial dynamics and patterns in megacities along the Belt and Road region using satellite imagery. Issue 1 (2nd January 2021) - Sun, Zhongchang; Yu, Sisi; Guo, Huadong; Wang, Cuizhen; Zhang, ZengXiang; Xu, Ru
ABSTRACT: The Belt and Road (B&R) region, a vital area with historical, economic, cultural and political significance, has undergone rapid urbanization in the past several decades, especially in the form of urban expansion. In this study, 20 megacities in the B&R region were selected to explore different spatiotemporal patterns of urban expansion. Object-oriented support vector machines (SVM), annual growth rate (AGR) models, and landscape metrics were employed to delineate the urban areas and characterize spatiotemporal characteristics and landscape patterns of these megacities during 1975–2015. All urban maps presented high overall accuracies (80.70%–95.90%) and overall Kappa coefficients (0.76–0.95). The study revealed that megacities in the B&R region have undergone different types of urban sprawl, mainly adopting a 'concentric circle' pattern in inland areas and a 'sector' pattern in coastal areas. Besides, six expansion modes were summarized according to the AGRs of individual megacities. Differences existed in megacities of the developing and developed countries and among five sub-regions. Moreover, 'dispersion, gathering, and re-dispersion' and 'coalescence' were two major landscape patterns of megacities in developing and developed countries. Results of this study can provide a scientific reference for urban planning and aid in sustainable development of local areas.